Collapse of Landau levels in graphene under uniaxial strain. (13th November 2019) - Ghosh, P; Roy, P
Abstract: We examine the collapse of Landau levels in graphene under uniform uniaxial strain and in the presence of a pair of crossed homogeneous electric and magnetic fields. In particular, we obtain the Landau levels and examine their dependence on the strain ϵ . It is shown that the Landau levels collapse when the magnitude of the electric field E reaches a critical value E c whose magnitude can be increased (decreased) by applying the strain in the zigzag (armchair) direction. We also examine the phenomena in the presence of crossed inhomogeneous fields.